2007
DOI: 10.1038/sj.bjc.6604142
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive epidermal growth factor receptor gene analysis from cytological specimens of non-small-cell lung cancers

Abstract: Epidermal growth factor receptor (EGFR) gene mutations and increased copy numbers are considered as predictors of response to EGFR tyrosine kinase inhibitors (EGFR-TKI) in non-small-cell lung cancer (NSCLC). Lung cancer diagnosis is often based on cytology alone. However, almost all published data on EGFR gene analyses were obtained from biopsies. This study tested the feasibility of EGFR gene analyses on cytological specimens. Eighty-four cytological specimens from NSCLCs were prospectively analysed for EGFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
4
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 40 publications
3
84
4
3
Order By: Relevance
“…They explained this fact by differences in the method of sample fixation between the two types of specimens, favoring methanol over formalin for mutational studies, thus highlighting the importance of preserving high-quality DNA. Savic et al [32] studied the presence of EGFR mutations in NSCLC samples, including some Papanicolau-stained slides from NSCLC patients, using sequencing methods. None of the previous studies provided clinical information on the outcome of the patients treated with TKIs to confirm their predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…They explained this fact by differences in the method of sample fixation between the two types of specimens, favoring methanol over formalin for mutational studies, thus highlighting the importance of preserving high-quality DNA. Savic et al [32] studied the presence of EGFR mutations in NSCLC samples, including some Papanicolau-stained slides from NSCLC patients, using sequencing methods. None of the previous studies provided clinical information on the outcome of the patients treated with TKIs to confirm their predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…Authors of the present study as well as other investigators (68)(69)(70) have demonstrated that EGFR mutation analysis may be performed on a small number of tumour cells (20-30 cells) isolated from a cytological slide, enabling the remaining material to be archived or used for other molecular analyses such as the EML4-ALK FISH test.…”
Section: Biological Samples Suitable For Molecular Characterisationmentioning
confidence: 99%
“…Efforts have therefore been focused on detection of EGFR mutations in cytological samples and the results of several studies have demonstrated that cytological material is suitable and reliable for EGFR mutation analysis (65)(66)(67)(68)(69)(70), such as that for the EML4-ALK FISH test (68). Specifically, paraffin-embedded histological or cytological sections could, compared to cytological smears, result in truncated cells and nuclei, producing more DNA fragmentation and a consequent possible false number of gene copies.…”
Section: Biological Samples Suitable For Molecular Characterisationmentioning
confidence: 99%
“…Безусловно, наилучшим биологиче-ским материалом для получения ДНК является операци-онный материал. Тем не менее различный цитологический материал, включая плевральные жидкости, может исполь-зоваться для молекулярных исследований [19,20]. Клеточ-ный материал, полученный при пункции опухоли легкого и ее метастазов (в том числе плеврального выпота) и брон-хоскопическом исследовании, может иметь гораздо больше опухолевых клеток, чем небольшая биопсия.…”
Section: Introductionunclassified